Application of mismatch equations in dynamic seating designs - Castellucci, Héctor Ignacio; Viviani, Carlos; Arezes, Pedro; Molenbroek, Johan F.M.; Martínez, Marta; Aparici, Verónica (My University, 2021)
Anthropometry is critical for product and workplace design. Highly prevalent, office work is associated with sedentarism and physical discomfort due to prolonged sitting. Dynamic seating (alternating across sitting, perching, and standing) has been suggested as an alternative to overcome those problems. The current study tested a large sample of anthropometric data for mismatch levels against national and international office furniture standards using dynamic seating as a framework with traditional and perching mismatch equations, applied to three recommended dynamic seating components. Dimensions present in the standards used did not match the majority of the sample. For sitting, seat width and depth individually presented the lowest levels of match, as well as under cumulative fit of all office furniture dimensions. However, these were alleviated when incorporating adjustability. Perching was shown to be generally impeded given commercially-available chair height options. Limitations in state-of-the-art perching equations are discussed, and two new models are proposed as design alternatives. Further research should focus on testing the criteria presented in this research through discomfort and objective measures.
Keywords: Perching; Sitting; Posture; Comfort; Office